Mouse model of postsurgical primary tumor recurrence and regional lymph node metastasis progression in HPV‐related head and neck cancer. Issue 12 (21st January 2018) - Mermod, Maxime; Hiou‐Feige, Agnès; Bovay, Esther; Roh, Vincent; Sponarova, Jana; Bongiovanni, Massimo; Vermeer, Daniel W.; Lee, John H.; Petrova, Tatiana V.; Rivals, Jean‐Paul; Monnier, Yan; Tolstonog, Genrich V.; et al.
Abstract : HPV‐positive head and neck squamous cell carcinoma (HNSCC) is increasingly frequent. Management is particularly debated in the case of postsurgical high‐risk features, that is, positive surgical margins and extracapsular spread (ECS). In this increasingly complex emerging framework of HNSCC treatment, representative preclinical models are needed to support future clinical trials and advances in personalized medicine. Here, we present an immunocompetent mouse model based on the implantation of mouse tonsil epithelial HPV16‐E6/E7‐expressing cancer cells into the submental region of the floor‐of‐the‐mouth. Primary tumors were found to replicate the patterns of human HNSCC local invasion and lymphatic dissemination. To study disease progression after surgery, tumors were removed likely leaving behind residual disease. Surgical resection of tumors was followed by a high rate of local recurrences (>90%) within the first 2–3 weeks. While only 50% of mice had lymph node metastases (LNM) at time of primary tumor excision, all mice with recurrent tumors showed evidence of LNM. To study the consecutive steps of LNM progression and distant metastasis development, LNs from tumor‐bearing mice were transplanted into naïve recipient mice. Using this approach, transplanted LNs were found to recapitulate all stages and relevant histological features of regional metastasis progression, including ECS and metastatic spread to the lungs. Altogether, we have developed an immunocompetent HPV‐positive HNSCC mouse model of postsurgical local recurrence and regional and distant metastasis progression suitable for preclinical studies. Abstract : What's new? Treatment failure in patients with head and neck squamous cell carcinomas (HNSCCs) positive for human papillomavirus (HPV) remains a problem. Preclinical models to evaluate new therapies for HPV‐positive HNSCC, however, are lacking. This report describes a novel orthotopic, immunocompetent mouse model of HPV‐related head and neck cancer for investigating local recurrence after surgery and extracapsular spread. Mice with established submental tumors frequently experienced local recurrence despite complete surgical resection. Moreover, both parental and derivative cell lines established invasive tumors in immunocompetent animals. The findings indicate that the new model can advance mechanistic understanding of HNSCC and potentially aid therapeutic development.